2017
DOI: 10.1111/dom.12918
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short‐term energy restriction on liver lipid content and inflammatory status in severely obese adults: Results of a randomized controlled trial using 2 dietary approaches

Abstract: Short-term very-low-energy diets (VLEDs) are used in clinical practice prior to bariatric surgery, but regimens vary and outcomes of a short intervention are unclear. We examined the effect of 2 VLEDs, a food-based diet (FD) and a meal-replacement plan (MRP; LighterLife UK Limited, Harlow, UK), over the course of 2 weeks in a randomized controlled trial. We collected clinical and anthropometric data, fasting blood samples, and dietary evaluation questionnaires. Surgeons took liver biopsies and made a visual as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 16 publications
(19 reference statements)
0
45
0
5
Order By: Relevance
“…This included 52% (16/31) of studies using a VLED and 85% (11/13) using an LED. Sufficient information on losses to follow‐up was provided by 26 studies; however, we found that in 15 of the 17 studies declaring any losses to follow‐up, participants were excluded from the analysis, with a median (IQR; range) of 4 (1‐8; 1‐14) participants dropping out . The remaining two studies opted for an intention‐to‐treat analysis, reporting 21 (14% of all participants) and four (4%) drop‐outs, respectively .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This included 52% (16/31) of studies using a VLED and 85% (11/13) using an LED. Sufficient information on losses to follow‐up was provided by 26 studies; however, we found that in 15 of the 17 studies declaring any losses to follow‐up, participants were excluded from the analysis, with a median (IQR; range) of 4 (1‐8; 1‐14) participants dropping out . The remaining two studies opted for an intention‐to‐treat analysis, reporting 21 (14% of all participants) and four (4%) drop‐outs, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…Patient characteristics such as age, sex and duration of diabetes, were included in 39, 39 and 28 studies, respectively, and drug treatment before and during the study in participants dropping out. 44,47,[50][51][52][53][54][55][56][57][58][59][60][61] The remaining two studies opted for an intention-to-treat analysis, reporting 21 (14% of all participants) and four (4%) drop-outs, respectively. 13,48 Adherence was not quantitatively or systematically assessed in the large majority of studies.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Despite its high prevalence and despite intensive research, the treatment of NAFLD remains an unmet medical need . Weight loss and exercise remain the cornerstones of its management, but both are difficult to achieve and sustain . Vitamin E improves hepatic steatosis and inflammation and may be administered in selected patients with NASH…”
Section: Introductionmentioning
confidence: 99%
“…The bariatric surgery team, hepatologists, histopathologists, molecular biologists and nutritionists/physiologists collaborated to undertake this study (Baldry et al . ). To examine the effects of the diets on the liver, biopsies of participants in the two diet groups were taken during surgery.…”
Section: My Own Research Experiencesmentioning
confidence: 97%
“…While there were no differences in liver fat content or indices of inflammation between the groups, the histological assessment of the liver biopsies showed lower levels of fat and less fibrosis than would be expected from people with this degree of obesity and not on a reduced energy diet (Baldry et al . ). These projects show the benefits of linking clinical practice and nutritional science to provide insights into the metabolic and nutritional disturbances seen in gastrointestinal and bariatric surgery patients.…”
Section: My Own Research Experiencesmentioning
confidence: 97%